Transperineal anal sphincter complex evaluation after obstetric anal sphincter injuries: With or without tomographic ultrasound imaging technique?. (February 2021) - Martinez Franco, Eva; Ros, Cristina; Santoro, Giulio Aniello; Cassadó Garriga, Jordi; Amat Tardiu, Lluís; Cuadras, Daniel; Espuña, Montserrat
Abstract: Objectives: "Significant" obstetric anal sphincter injuries (OASIS) have been defined as visible defects of at least 30° in at least 4/6 slices using tomographic ultrasound imaging (TUI) with transperineal ultrasound (TPUS). The objective of this study was to assess if TUI is mandatory for the evaluation of OASIS. Methods: Patients with a history of OASIS were evaluated by performing 3D-endoanal ultrasound (EAUS) and 3D-TPUS with and without TUI. Any damage to the internal (IAS) or external (EAS) anal sphincters was recorded and scored using the Starck's and the Norderval's systems. Intraobserver and inter-techniques correlations were calculated. Results: From September 2012 to May 2015, 63 women, mean age 32.5 ± 4.6 years, with OASIS (3a: 26 pts., 41.3 %; 3b: 26 pts., 41.3 %; 3c: 6 pts., 9.5 %, 4: 4 pts., 6.3 %, "button hole" tear: 1 pt., 1.6 %). Inter-technique and intraobserver correlations were excellent (TUI: k = 0.9; sweeping technique: k = 0.85; EAUS: k = 0.9) in determining OASIS. Using the Starck's Score, excellent correlation was found for both TPUS modalities (TUI: k = 0.86; sweeping technique: k = 0.89). However, for the different individual parameters, the correlation was moderate for EAS depth (TUI: k = 0.44; sweeping technique: k = 0.5) and good for IAS depth (TUI: k = 0.7; sweeping technique: k = 0.78). Similar results were found using the Norderval's classification. Conclusions: OASIS can be assessed by TPUS without TUI technique, dragging the rendered box and following the anal canal from the anal verge to the anorectal junction in the longitudinal plane and describing findings.